2019
DOI: 10.1111/pbi.13267
|View full text |Cite
|
Sign up to set email alerts
|

The retromer protein ZmVPS29 regulates maize kernel morphology likely through an auxin‐dependent process(es)

Abstract: Summary Kernel size and morphology are two important yield‐determining traits in maize, but their molecular and genetic mechanisms are poorly characterized. Here, we identified a major QTL, qKM4.08, which explains approximately 24.20% of the kernel morphology variance in a recombinant population derived from two elite maize inbred lines, Huangzaosi (HZS, round kernel) and LV28 (slender kernel). Positional cloning and transgenic analysis revealed that qKM4.08 encodes ZmVPS29, a retromer complex component. Compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Plant hormones are one of the most important factors affecting the growth and development of grains [ 23 , 24 ]. Cytokinin and brassinolide play a vital role in regulating seed size, auxin, ABA, and gibberellin have regulatory effects on seed development to a certain extent [ 25 ]. Through transcriptomics analysis, we found that the signal transduction pathway has a notable influence on grain size.…”
Section: Discussionmentioning
confidence: 99%
“…Plant hormones are one of the most important factors affecting the growth and development of grains [ 23 , 24 ]. Cytokinin and brassinolide play a vital role in regulating seed size, auxin, ABA, and gibberellin have regulatory effects on seed development to a certain extent [ 25 ]. Through transcriptomics analysis, we found that the signal transduction pathway has a notable influence on grain size.…”
Section: Discussionmentioning
confidence: 99%
“…The retromer components VPS35A and VPS29 are essential for normal prevacuolar compartment morphology and normal trafficking of plasma membrane proteins in plants (Nodzyński et al 2013). A recent study showed that ZmVPS29 is involved in auxin accumulation during early kernel development in maize (Chen et al 2020). An evolutionarily conserved VPS26 protein (VPS26C; At1G48550) functions in a complex with VPS35A and VPS29, which are necessary for root hair growth in Arabidopsis (Jha et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Many genes related to plant hormones have been con rmed to play key roles in regulating plant kernel development [20]. In recent years, it has been discovered that cytokinin and brassinolide play a vital role in regulating seed size, and in addition, auxin, ABA, and gibberellin have regulatory effects on seed development to a certain extent [21]. In this study, we detected changes in IAA, GA3, CTK, and BR during grain development in Chang 7 − 2 and TC19.…”
Section: Discussionmentioning
confidence: 99%